(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Neural tube defects are common congenital anomalies seen most commonly among population of low socio-economic status. These anomalies range from spina bifida occulta to craniorachischisis totalis and iniencephaly, which are very rare conditions. In many cases neural tube defects are associated with other malformations. Neural Tube Defects are seen mostly affecting first pregnancy. Neural Tube Defects are seen in all corners of the world. India also has quite high incidence, and in many cases it is due to folic acid deficiency. Here we present a case of Craniorachischisis totalis (Anencephaly with spina bifida aperta) in a 32 week gestation male fetus, born as fourth child to a Muslim mother. Academic autopsy was performed to see the presence of other associated congenital malformations, if any.